Enzymatic Reduction of Sugar Content in Sucrose-Rich Fruit Products - Tiago Durães; Miguel Azevedo; Fernanda Cosme; Fernando M. Nunes (Medical Sciences Forum)
Sugar is essential to organisms, but excessive consumption can lead to certain diseases. Overconsumption is a major concern in modern society, especially in developed countries. The purpose of this study was to convert sucrose present in sucrose-rich fruit concentrates into fructooligosaccharides (FOS) using the enzymes invertase (Inv) or fructosyltransferase (FTase). FOS are oligosaccharides (OS) that bypass part of the digestive system and reach the colon, where they are metabolized by gut bacteria. This can simultaneously exert prebiotic effects while reducing a product’s calories. Based on these results, it was concluded that there is potential for enzymatically reducing a product’s caloric value while converting sucrose into FOS, thus enriching the product’s dietary fiber content.